Ukraine : 2005 Article IV Consultation and Ex Post Assessment of Longer-Term Program Engagement; Staff Reports; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2005)
This paper focuses on Ukraine's 2005 Article IV Consultation and Ex Post Assessment of Longer-Term Program Engagement. After four years of strong activity, annual growth has slowed sharply, from a peak of about 12 percent in 2004 to 3 percent for January-September 2005. Fiscal policy in 2005 has aimed at a significant fiscal tightening, with the supplementary 2005 budget targeting a general government deficit of 2 1\2 percent of GDP compared with the 4 1\2 percent of GDP realized during 2004, and the 6-7 percent of GDP implicit in the original 2005 budget.